2001
DOI: 10.1007/s00203-001-0355-5
|View full text |Cite
|
Sign up to set email alerts
|

Preparative isolation of lipid inclusions from Rhodococcus opacus and Rhodococcus ruber and identification of granule-associated proteins

Abstract: Triacylglycerol granules synthesized and accumulated by Rhodococcus opacus and Rhodococcus ruber were isolated by glycerol density gradient centrifugation. Whereas only one type of granule could be isolated from R. opacus, two types of granules with different specific densities were isolated from R. ruber. Both types of R. ruber granules showed a similar content of triacylglycerols and poly(3-hydroxybutyrate- co-3-hydroxyvalerate), but the protein profiles of both types were significantly different. The granul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 35 publications
1
37
0
Order By: Relevance
“…Similar studies involving the isolation and proteomic analysis of lipid-containing granules/lipid inclusions from Rhodococcus opacus PD630 and Rhodococcus ruber have previously been carried out ( 42 ). When the lipid inclusions of these two bacteria were isolated, they were also found to contain a large number of proteins.…”
Section: Deletion Of Ro02104 Increases the Size Of Ldsmentioning
confidence: 54%
“…Similar studies involving the isolation and proteomic analysis of lipid-containing granules/lipid inclusions from Rhodococcus opacus PD630 and Rhodococcus ruber have previously been carried out ( 42 ). When the lipid inclusions of these two bacteria were isolated, they were also found to contain a large number of proteins.…”
Section: Deletion Of Ro02104 Increases the Size Of Ldsmentioning
confidence: 54%
“…However, it was not until recent proteomic, biochemical, and molecular studies in bacteria that this conservation across species was demonstrated to extend into the prokaryotic kingdom. The earliest of the studies on bacterial lipid droplets was conducted with Rhodococcus ruber ( 42 ). The isolated fraction was defi ned as "lipid inclusions."…”
Section: Bacteriamentioning
confidence: 99%
“…It was observed that another ribosomal protein L7 was found to be copurified with the lipid inclusion bodies obtained from oleaginous bacteria like Rhodococcus opacus PD360 and Rhodococcus ruber. The significance of this association is not clear (32).…”
Section: Discussionmentioning
confidence: 95%
“…The cDNA library construction kit was from Stratagene (La Jolla, CA). [1-14 C]Palmitoyl-CoA (51 mCi/mmol), [1-14 C]oleic acid (55 mCi/mmol), and [␣- 32 P]dATP/dCTP (30 Ci/mmol) were obtained from PerkinElmer Life Sciences. Restriction enzymes, deoxynucleotidyl terminal transferase, Pfu polymerase, low melting agarose, deoxynucleotidyl triphosphates, Sephadex G-10, G-50, EDTA, isopropyl-␤-D-thiogalactopyranoside (IPTG), 5-bromo-4-chloro-3-indolyl-␤-D-galactopyranoside (X-gal), and all other molecular biology reagents were from Amersham Biosciences.…”
Section: Materials-r Glutinis Was Obtained From the Institute Of Micmentioning
confidence: 99%